Determinan Nilai Perusahaan Sektor Properti dan Real Estate di Bursa Efek Indonesia - Kamila, Vennia; Nurmatias, Nurmatias (E-Jurnal Akuntansi, 2022)
The purpose of this research is to analyze the effect of profitability, structure and interest rate on firm value. The research population is property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. By using purposive sampling, 44 property and real estate companies with a five year period of research obtained 220 units of observation. The data analysis technique uses Panel Data Regression Analysis with the application of the E-Views 12 program with a significance level of 5%. This study shows the results that profitability, capital structure and interest rates have a significant positive effect on firm value. Keywords: Profitability; Capital Structure; Interest Rate; The Value Of The Company.